2008
DOI: 10.1002/app.28420
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of chitosan‐modified poly(acrylic acid)

Abstract: Potassium persulfate (K 2 S 2 O 8 ) was used to initiate the polymerization of acrylic acid (AA) monomer in a chitosan (CS) solution. Both a poly(acrylic acid) (PAA) homopolymer and a CS-co-PAA copolymer were produced. When the amount of AA was increased from 5 to 40 g with 5 g of CS, the total monomer conversion was found to increase from 89 to 98% after 2 h of reaction at 708C. In addition, the percentage of reacted AA monomer being converted to the CS-co-PAA copolymer (copolymerization efficiency) and the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…However, in the previous studies, it was found that the anionic sulfate radical ( • SO 4 − ) can degrade one CS chain into two shorter chains. One has a terminal carbonyl group and the other has a free radical at the scission end 27, 28. It is thus expected that if KPS was used to initiate the polymerization in the present system, it could also degrade CS and thus produce CS chain radical.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…However, in the previous studies, it was found that the anionic sulfate radical ( • SO 4 − ) can degrade one CS chain into two shorter chains. One has a terminal carbonyl group and the other has a free radical at the scission end 27, 28. It is thus expected that if KPS was used to initiate the polymerization in the present system, it could also degrade CS and thus produce CS chain radical.…”
Section: Resultsmentioning
confidence: 91%
“…It is thus expected that if KPS was used to initiate the polymerization in the present system, it could also degrade CS and thus produce CS chain radical. Subsequently, AA was able to grow on the CS chain radical to produce CS‐ co ‐PAA copolymer, in addition to the PAA homopolymer 28. Furthermore, when the extent of polymerization reached a certain level, polyelectrolyte complex would be formed between positively charged CS and negatively charged PAA chains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations